The Influence of Individual Characteristics and Organizational Commitment on The Performance of Police Personnel in The Rawamerta Sector of Karawang Regency, West Java - Ulan Sonjaya; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Management Science, 2026)
The objectives of this study are to examine the influence of individual characteristics on personnel performance, the influence of organizational commitment on personnel performance, and the simultaneous influence of individual characteristics and organizational commitment on the performance of Rawamerta Sector Police personnel. The t-value for variable X1 (Individual Characteristics) was 4.334. while the ttable value for n = 46 is 2.013. So tcount > ttable or 4.334 > 2.013, it can be concluded that partially the individual Characteristics variable has a positive effect on personnel Performance, the tcount value for variable X2 (Organizational Commitment) is 6.703, while the ttable value for n = 46 is 2.013. So tcount > ttable or 6.703 > 2.013, it can be concluded that partially the organizational Commitment variable has a positive effect on personnel Performance. The ANOVA test obtained an Fcount value of 66.455 which is greater than the Ftable for n = 46 of 2.81 with a significant level of 0.000 because 0.000 <0.05, it can be said that individual Characteristics (X1) and Organizational Commitment (X2) together have a positive effect on personnel Performance (Y).